Therapeutic strategies for EGFR-mutated non-small cell lung cancer patients with osimertinib resistance - Fu, Kai; Xie, Fachao; Wang, Fang; Fu, Liwu (Journal of hematology and oncology, 2022)
Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are the preferential options for advanced non-small cell lung cancer (NSCLC) patients harboring EGFR mutations. Osimertinib is a potent irreversible third-generation EGFR-TKI targeting EGFR mutations but has little effect on wild-type EGFR. In view of its remarkable efficacy and manageable safety, osimertinib was recommended as the standard first-line treatment for advanced or metastatic NSCLC patients with EGFR mutations. However, as the other EGFR-TKIs, osimertinib will inevitably develop acquired resistance, which limits its efficacy on the treatment of EGFR-mutated NSCLC patients. The etiology of triggering osimertinib resistance is complex including EGFR-dependent and EGFR-independent pathways, and different therapeutic strategies for the NSCLC patients with osimertinib resistance have been developed. Herein, we comprehensively summarized the resistance mechanisms of osimertinib and discuss in detail the potential therapeutic strategies for EGFR-mutated NSCLC patients suffering osimertinib resistance for the sake of the improvement of survival and further achievement of precise medicine.